Enhancing Family Welfare: Women Vegetable Traders’ Contribution at Namlea Market in Buru Regency - Tobondo, Adriani Galry Adoniram (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
The aim of this research is to describe the efforts of female vegetable vendors in the Namlea market to improve their family's well-being and to identify the inhibiting factors affecting these efforts. The research methodology employed is qualitative description, with data collection techniques including observation, interviews, and documentation. The research findings indicate that female vegetable vendors make various efforts to enhance their family's well-being, such as establishing food stalls, selling cendol, adding vending stalls, marketing staple foods, and offering sewing services. However, the improvement of the family's well-being is hindered by factors such as limited educational attainment, which restricts their skills, limited business capital, and a shortage of human resources within the family. This understanding holds significant implications for endeavors to enhance the economic conditions of families in the Namlea market.